Histone Deacetylase Inhibitors in Cancer Therapy - Sun, Yijie; Sun, Yanyi; Yue, Saichao; Wang, Yaohe; Lu, Fanghui (Current Topics in Medicinal Chemistry, 2018)
Histone deacetylases (HDACs), as epigenetic modifiers, are essential for gene transcriptional activities. The alternation of HDACs expression, mutation and/or inappropriate recruitments has been discovered in a broad range of tumors contributing to the tumorigenesis through a serial of biological pathways. HDACs, therefore, are characterized as promising cancer therapeutic targets, and their inhibitors are under rapid development. Here, we discuss HDAC inhibitors in terms of their functional mechanism establishing the anti-tumor effects and potential clinical applications including the synergistic effects in combinational treatment.
Keywords: Cancer treatment